Estudo da rima palpebral de pacientes operados de estrabismo: uma análise por processamento digital de imagem - Lima, Luiz Cláudio Santos de Souza (2010)
PURPOSE: To evaluate the relationship between horizontal strabismus surgery and chances in palpebral fissure width. DESIGN: Interventional case series. METHODS: We compared Pre- and pos-operative lid fissure widths in 71 patients of the 130 eyes in prospective, nonrandomized consecutive strabismus surgeries, subdivided into four groups with comitant deviation. A digital imaging process analysis of the lid fissure width was used before and after all unilateral or bilateral recessions of the medial or lateral rectus muscles and monocular recession-resection surgery for the correction of esotropia (ETRM group, n= 79 eyes) and exotropia (XTRL group, n= 25 eyes); and for esotropic (ETRR group, n= 14 eyes) and exotropic (XTRR group, n=12 eyes). RESULTS: The ETRM group has increased the lid fissure ranging 0.6 2.5 mm (average 0.9 mm; SD = 1.0); XTRL between 0.2 to 3.2 mm (average 1.0 mm; SD = 1.0); ETRR variation 0.0 to 2.3 mm (average 0.9 mm; SD = 0.6) and XTRR-1.6 1.4 (average = 0.2 mm; SD = 0.9). The difference between pre- and post-operative palpebral fissure widths was statistically significant (p < .0001, t-test) in the two treatment recession groups. The percentage of average increase in the recess group was 11.9 and 11.8% for ETRL and XTRL respectively. There were no significant differences for the groups ETRR and XTRR (p value = 0.0634, test t).CONCLUSIONS: Unilateral or bilateral recession of the rectus muscles for horizontal comitant strabismus may result in widening of the palpebral fissure. No significant chances in palpebral fissure occurred following recess-resect procedures.